The Role of Job Satisfaction as a Mediator in the Influence of Talent Management and Career Development on Employee Performance: A Study of Polri Institutions in Central Java - Dian Puji Lestari; Jati Waskito (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Talent management and career development are important factors in improving employee performance in various organizations, including government institutions. This study discusses the relationship between these two factors with employee job satisfaction and performance, as well as the role of job satisfaction as a mediator in the relationship. This study aims to explore the relationship between talent management, career development, and job satisfaction on employee performance at the National Police Institution in Central Java. Within this framework, job satisfaction is examined as a mediating variable. Using a quantitative approach by distributing questionnaires to 130 respondents, data analysis was conducted using the Partial Least Squares (PLS) method. The results of the study indicate that talent management and career development significantly affect employee job satisfaction and performance. In addition, job satisfaction is proven to mediate the relationship between talent management and employee performance, but not career development and employee performance. These findings highlight the importance of effective human resource management strategies to improve employee job satisfaction and performance. This study also provides practical implications, especially for the National Police institution, to optimize training programs, career development, and a supportive work environment.